Economic stimuli as motivation for academic excellence in students of the "Almirante Illingworth" Higher University Institute - Balbin Mantilla, Mariuxi Cecilia; Cuji Rosales, Karina Margoth (Revista Minerva, 2023)
The objective of this paper is to highlight the importance of economic incentives as a motivation for academic excellence at the Almirante Illingworth Higher University Institute (AITEC), this being a benefit not only for the students but also for the institution, since the granting of scholarships through different criteria offered by the institute, academic excellence has significantly improved from 2016 to the present, a study that was carried out using quantitative and qualitative methods, through information obtained from the SIGIA repository and the interviews carried out with the students during the years that scholarships have been awarded respectively, as well as through bibliographical research of previous studies, as a basis for the research. Concluding that the economic stimuli encourage motivation for academic excellence for the professional training of students in the different careers offered by the institute, guaranteeing equal opportunities in their higher level academic training, for their continuity and completion of their career. Allowing the institute to offer professionals trained and prepared to be part of the labor field or generation of enterprises, improving their quality of life.
Keywords: Academic excellence; economic incentives; motivation; higher level students